Aeromonas Diversity and Antimicrobial Susceptibility in Freshwater—An Attempt to Set Generic Epidemiological Cut-Off Values - Baron, Sandrine; Granier, Sophie A.; Larvor, Emeline; Jouy, Eric; Cineux, Maelan; Wilhelm, Amandine; Gassilloud, Benoit; Le Bouquin, Sophie; Kempf, Isabelle; Chauvin, Claire (Frontiers in Microbiology, 2017)
The importance of the role of environment in the dissemination of antimicrobial resistant bacteria is now well recognized. Thus, bacterial indicators to monitor the phenomena are required. The Aeromonas genus is autochthonous in the aquatic environment and easy to detect in any water type, such as freshwater or wastewater. These microorganisms are also causing infections in humans and animals (including fish). Furthermore, as Aeromonas spp. is able to acquire antimicrobial resistance mechanisms, it is candidate for indicator bacteria to follow antimicrobial resistance dissemination in aquatic environments. Unfortunately, to date, interpretation criteria for Aeromonas spp. for antimicrobial susceptibility tests are scarce in the literature. No epidemiological cut-off values for Aeromonas are currently available at EUCAST to interpret Minimum Inhibitory Concentrations (MIC). The only interpretation criteria available are clinical breakpoints from CLSI that are adapted from Enterobacteriaceae. Based on the results of MIC distributions obtained for a collection of environmental isolates of Aeromonas, this study aimed at proposing tentative epidemiological cut-off values (COWT) for Aeromonas spp. assessing whether the genus is an acceptable level of definition. Thus, 233 isolates collected from 16 rivers were identified at species level using Maldi-Tof (Bruker). Eleven different species were identified, the most abundant were A. bestiarum (n=54), A. salmonicida (n=45), A. sobria (n=41) and A. eucrenophila (n=37). 96-well micro plates containing different concentrations of 15 antimicrobials, namely cefotaxime, ceftazidime, chloramphenicol, colistin, enrofloxacin, erythromycin, florfenicol, flumequine, gentamicin, nalidixic acid, oxolinic acid, streptomycin, temocillin, tetracycline and trimethoprim-sulfamethoxazole, were prepared. The broth micro-dilution method was used to determine the antimicrobial susceptibility of each isolate. The estimation of COWT values was satisfactory obtained at genus level for all antimicrobials except cefotaxime and erythromycin. This first step is an invitation for other research teams to increase the amount of antimicrobial resistance data collected. Then, robustness of our proposed provisional generic epidemiological cut-off values could be assessed by testing antimicrobial susceptibility of various Aeromonas collections.